Nickel-based alloy flux-cored wire for dredging pipeline welding, preparation method and welding method
By using nickel-based alloy flux-cored welding wire with specific composition and TIG welding process, the problem of insufficient wear resistance and corrosion resistance in dredging pipeline welding has been solved, achieving high hardness and long service life of the weld, and adapting to the welding requirements of complex working conditions.
Patent Information
- Application Number
- CN202511547974.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-28
- Publication Date
- 2025-11-28
AI Technical Summary
Existing welding wires for dredging pipelines are insufficient in terms of wear resistance and corrosion resistance, failing to meet the requirements for long-term service. Furthermore, problems such as weld slag residue and hot cracking are prone to occur during the welding process.
Using nickel-based alloy flux-cored welding wires with specific compositions, including Ni, Cr, Mo, W, Cu, Si, Mn, CaCO3, CaF2, and TiO2, a stable hard phase and protective film are formed through TIG welding, which improves the wear resistance and corrosion resistance of the weld and optimizes the welding process to reduce defects.
It significantly improves the hardness and wear resistance of welds, extends service life, reduces weld slag residue and the risk of hot cracking, adapts to complex dredging conditions, and meets the long-term service requirements of marine environments.
Smart Images

Figure CN121017916A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of welding materials, and relates to a nickel-based alloy flux-cored wire for dredging pipeline welding, a preparation method and a welding method. BACKGROUND
[0002] As a core link of river dredging, port construction and channel maintenance, the service environment of the dredging pipeline in the conveying system is extremely challenging. Such a pipeline needs to transport solid-liquid mixtures containing hard particles such as silt and stones for a long time, and also needs to be in contact with seawater, salt mist and corrosive slurry containing sulfate and chloride ions in coastal or marine engineering, which causes the pipeline welded joint to become a weak link of the system. According to the operation and maintenance data of dredging engineering, more than 60% of pipeline failures are caused by wear and tear or corrosion cracking of the welded joint, which not only increases the operation and maintenance cost, but also may cause environmental pollution risk due to slurry leakage.
[0003] Currently, two types of welding wires are mainly used for dredging pipeline welding: one type is ordinary carbon steel or low alloy steel welding wire, which has low cost but poor corrosion resistance of the weld, and the service period in the marine environment is usually less than 6 months, and the wear resistance is weak, and local wear and tear perforation easily occurs when facing silt scouring; the other type is conventional nickel-based alloy welding wire (such as ERNiCrMo-3, ERNiCr-3 series), which has certain corrosion resistance, but its composition design is not optimized for dredging conditions - most conventional nickel-based welding wires do not contain tungsten element, and the surface hardness of the weld is only HV250-HV280, and the wear resistance is insufficient, and in high-concentration silt conveying scenarios, the joint wear rate is 0.15-0.2 mm / month, and it needs to be replaced after 1-2 years of service; at the same time, the flux core of some conventional welding wires uses acidic or neutral slag system, and the chromium element burnout rate is as high as 8%-12% during welding, which causes the actual chromium content of the weld to be lower than the design value, and the corrosion rate in 3.5% sodium chloride solution is 0.05-0.08 mm / year, which is difficult to meet the service requirement of more than 5 years of marine dredging pipeline.
[0004] Although the existing patent technology improves the performance of the welding wire, there are still obvious limitations: for example, some patents (such as CN102962603B) improve the corrosion resistance by increasing the molybdenum content (9%-10%), but do not consider the wear resistance, and high molybdenum content significantly increases the cost of the welding wire; another patent (such as CN105643141B) uses vanadium and niobium elements to strengthen the hardness of the weld, but it is easy to cause welding hot cracks, and is not suitable for field welding; there is also a patent (such as CN104342584A) whose flux core does not add rare earth elements, and the weld has coarse grains and insufficient low-temperature impact toughness (-40℃ impact energy ≤40J), which is easy to cause brittle fracture under the vibration load of dredging operation. In addition, the slag removal rate of most existing flux-cored wires is less than 90%, and in the commonly used welding positions such as vertical welding and horizontal welding in pipeline field, it is easy to produce slag residues, which affects the joint sealing and subsequent corrosion prevention treatment. SUMMARY
[0005] The purpose of the present application is to provide a nickel-based alloy flux-cored wire for dredging pipeline welding, which solves the problems of insufficient wear resistance, poor corrosion resistance and weak process adaptability of conventional welding wires in dredging pipeline welding, and meets the demand of long service life and high reliability of pipeline welding joints in dredging engineering.
[0006] The present application can greatly prolong the service life and reduce maintenance costs, and improve the efficiency and safety of the engineering.
[0007] The second purpose of the present application is to provide a preparation method of the above-mentioned nickel-based alloy flux-cored wire for dredging pipeline welding.
[0008] The third purpose of the present application is to provide a welding method of the above-mentioned nickel-based alloy flux-cored wire for dredging pipeline welding.
[0009] The technical scheme adopted by the present application is: a nickel-based alloy flux-cored wire for dredging pipeline welding, comprising a sheath and a core, the core comprising the following components in mass percentage: Ni: 58.0%-60.0%, Cr: 18.0%-20.0%, Mo: 4.5%-5.5%, W: 2.0%-3.0%, Cu: 1.0%-1.5%, Si: 0.8%-1.2%, Mn: 0.5%-0.8%, CaCO3: 3.5%-4.0%, CaF2: 2.0%-2.5%, TiO2: 1.0%-1.5%, and the balance being unavoidable impurities.
[0010] The powder particle size in the core is greater than 100 mesh.
[0011] The sheath is an Inconel 625 nickel-based alloy strip with a width of 7 mm and a thickness of 0.3 mm.
[0012] The filling rate of the core powder in the sheath is 18wt%-25wt%.
[0013] A preparation method of a nickel-based alloy flux-cored wire for dredging pipeline welding, comprising: Step 1, respectively take the following core powder according to mass percentage: Ni: 58.0%-60.0%, Cr: 18.0%-20.0%, Mo: 4.5%-5.5%, W: 2.0%-3.0%, Cu: 1.0%-1.5%, Si: 0.8%-1.2%, Mn: 0.5%-0.8%, CaCO3: 3.5%-4.0%, CaF2: 2.0%-2.5%, TiO2: 1.0%-1.5%, and the balance being unavoidable impurities; The powder particle size in the core is greater than 100 mesh. Step 2, the weighed drug core powder in step 1 is dried; Specifically: heating to 160-210 DEG C in a vacuum tube furnace, and keeping for 2-3 hours; Step 3, the dried drug core powder in step 2 is loaded in a stirring bottle, and then is stirred in a V-shaped mixer for 20-40 minutes, at a stirring speed of 10-30 rpm, until the stirring is uniform; Step 4, the drug core powder prepared in step 3 is filled into a U-shaped welding sheath, and the sheath is closed by a mold to obtain a raw welding wire; Step 5, the raw welding wire is made into a nickel-based alloy cored wire for dredging pipeline welding by a step-by-step reducing method.
[0014] The dredging pipeline welding method adopts the nickel-based alloy cored wire for dredging pipeline welding, and comprises the following steps: Step 1), setting the parameters of a TIG welding device; Step 2), according to the welding current size and the material of the welding piece, selecting a tungsten electrode and a nickel-based alloy cored wire, and adjusting the protective gas; Step 3), welding the welding piece under the protective gas.
[0015] In step 1, the voltage is 12-16 V, the current is 110-180 A, and the wire dry extension is 8-15 mm.
[0016] In step 2, the protective gas is argon, and the flow rate is controlled at 5-15 L / min.
[0017] The present application has the following effects: 1. The present application provides a nickel-based alloy cored wire for dredging pipeline welding, which has a short preparation period, high production efficiency, and can realize batch production. 2. The present application has good processability and good weld forming. Special alloy components are added to the cored wire, which can form hard carbides or other hard phases and laves phases during welding, significantly improving the hardness and wear resistance of the weld layer.
[0018] 3. The present application provides a TIG welding process, and the cored wire is used as a raw material. The cored wire is uniform and the arc is stable during welding, which can well improve the wear resistance and service life of the weld, and the weld is formed with good appearance and basically no collapse. BRIEF DESCRIPTION OF DRAWINGS
[0019] Figure 1 is the microstructure diagram of example four of the present application. DETAILED DESCRIPTION
[0020] The application will be described in detail below with reference to the accompanying drawings and specific embodiments.
[0021] The first technical solution of the application is a nickel-based alloy flux-cored wire for dredging pipeline welding, comprising a sheath and a core, the core is composed of the following components in mass percentage: Ni: 58.0%-60.0%, Cr: 18.0%-20.0%, Mo: 4.5%-5.5%, W: 2.0%-3.0%, Cu: 1.0%-1.5%, Si: 0.8%-1.2%, Mn: 0.5%-0.8%, CaCO3: 3.5%-4.0%, CaF2: 2.0%-2.5%, TiO2: 1.0%-1.5%, and the balance is inevitable impurities, but the total amount of impurities is controlled below 0.5%.
[0022] The particle size of the powder in the core is greater than 100 mesh; The sheath is an Inconel 625 nickel-based alloy strip, with a width of 7 mm and a thickness of 0.3 mm; The filling rate of the core powder in the sheath is 18wt%-25wt%.
[0023] The roles of each component in the core are as follows: Ni: Ni (nickel) is the first core builder of the corrosion-resistant matrix of the weld. In the working condition of the dredging pipeline contacting seawater and chlorine ion-containing slurry, Ni can form a dense oxidation protective film on the surface of the weld, blocking the penetration of corrosive media; at the same time, high content of Ni (65.0%-68.0%) ensures that the weld metal has a stable face-centered cubic crystal structure, avoiding local corrosion caused by crystal defects, and providing structural support for the subsequent corrosion-resistant elements such as Cr and Cu, which is different from the existing patent which only emphasizes the "basic corrosion resistance" of Ni, and highlights the support value of Ni to the corrosion-resistant system. Secondly, Ni realizes synergistic effect with wear-resistant elements. In this patent, Ni can form stable intermetallic compounds (such as Ni3W, NiMo) with W (2.0%-3.0%) and Mo (4.5%-5.5%), these hard phases are uniformly dispersed in the Ni matrix, which not only improves the surface hardness of the weld (HV320-HV350), but also avoids the decrease of toughness caused by the aggregation of hard phases, solving the pain point of "difficult to balance wear resistance and toughness" in the welding of dredging pipelines, and the existing public content rarely mentions the synergistic regulation of Ni on wear-resistant elements.
[0024] Cr: Cr (chromium) is the key element to ensure the synergistic performance of corrosion resistance and wear resistance of the weld. On the one hand, Cr forms a dense Cr2O3 passivation film on the surface of the weld, which can block the penetration of seawater and chloride-containing slurry, and cooperates with the Ni matrix to enhance the stability of the film layer, solving the problem of easy peeling of the film layer of conventional welding wire; on the other hand, Cr cooperates with the supplemented metal chromium powder in the core to make up for the loss of Cr during welding, ensuring that the Cr content of the weld meets the standard, and cooperates with Mo and W to improve the uniformity of hard phase distribution, avoiding excessive local wear and adapting to the double working conditions of silt scouring and seawater corrosion of the dredging pipeline.
[0025] Mo: Mo (molybdenum) is the core synergistic element to realize the dual performance of "pitting corrosion resistance + wear resistance" of the weld, which focuses on the special service requirements of the dredging pipeline. On the one hand, Mo can cooperate with Cr to strengthen the corrosion resistance of the weld, in seawater and chloride-containing slurry, Mo can promote the repair of Cr2O3 passivation film, inhibit the corrosion of chloride ions to the film layer, reduce the risk of pitting corrosion and crevice corrosion of the weld, and cooperate with the metal molybdenum powder in the core to make up for the loss during welding, ensuring the stability of the corrosion resistance of the weld; on the other hand, Mo can cooperate with Ni and W to improve the wear resistance of the weld, after Mo atoms are integrated into the Ni matrix, they can form Ni3W-MoC composite hard phase with W, not only enhancing the bonding force of the hard phase to avoid the peeling of the hard phase during wear, but also refining the hard phase particles, so that the hardness of the weld is uniformly maintained at HV320-HV350, adapting to the silt scouring condition; at the same time, Mo can reduce the brittleness of the weld metal, cooperate with rare earth elements to refine the grain, avoid the cracking of the welded joint under vibration load, and ensure the long-term service reliability of the dredging pipeline.
[0026] W: W (tungsten) is the key functional element to solve the problem of "wear resistance and toughness balance" of the weld, which focuses on the special requirements of silt scouring of the dredging pipeline. On the one hand, W can cooperate with Ni to form Ni3W hard phase, which has a hardness of HV450 or above, and after being uniformly dispersed in the Ni matrix, it can improve the overall hardness of the weld surface to HV320-HV350, which is more than 25% higher than that of conventional nickel-based welding wire, effectively resisting the scouring and wear of hard particles in silt, and avoiding the perforation failure of the pipeline joint due to local wear; on the other hand, the addition of W can avoid the welding hot cracking problem easily caused by other wear-resistant elements (such as V, Nb), the composite hard phase (Ni3W+MoC) formed by W and Mo (4.5%-5.5%) can reduce the agglomeration of hard phase, cooperate with rare earth elements to refine the grain, ensure that the weld still has good toughness (impact energy ≥60J at-40℃) on the basis of high hardness, solve the problem of brittle fracture of the weld under the vibration load of dredging operation; at the same time, W has strong stability during welding, with a loss rate of less than 3%, without the need for additional large amount of supplementation, reducing the complexity of the core formulation, which is the process adaptation advantage of W that existing public content does not involve.
[0027] Cu: Cu (copper) is a key element to strengthen the corrosion resistance of the weld seam in seawater, and to make up for the short board of the conventional corrosion-resistant system. Its role focuses on the marine service scene of the dredging pipeline. On the one hand, Cu can cooperate with Ni and Cr to build a "multi-layer protection system" and form a dense Cu2O film on the surface of the weld seam. This film can complement the Cr2O3 passivation film, further block the corrosion of seawater and chloride ions to the weld seam matrix, especially in the presence of sulfate in the dredging slurry, which can effectively reduce the electrochemical corrosion rate and make the corrosion rate of the weld seam stable at ≤0.02 mm / year, solving the problem of insufficient protection of conventional welding wire in complex corrosion environments. On the other hand, the addition of Cu can optimize the electrochemical properties of the weld seam and reduce the potential difference between the weld seam and the pipeline base material, avoiding joint failure due to galvanic corrosion, which is not covered by existing public content. At the same time, the content of 1.0%-1.5% Cu can avoid the risk of weld heat cracking caused by excessive addition, and cooperate with the refining effect of rare earth elements in the flux to ensure that the weld still maintains good mechanical properties on the basis of high corrosion resistance, adapting to the vibration operation conditions of the dredging pipeline.
[0028] Si: Si (silicon) is a key element that takes into account the purity of the weld seam, process adaptability and performance synergy, and its role focuses on the special needs of the welding of the dredging pipeline. On the one hand, as an efficient deoxidizer, Si can combine with oxygen in the molten pool to form SiO2 during welding, and cooperate with the strong deoxidizing effect of aluminum powder to control the oxygen content of the weld seam below 0.015%, reducing defects such as pores and slag, and avoiding corrosion hazards caused by defects, which is crucial for the weld seam of the dredging pipeline that is in contact with seawater for a long time. On the other hand, Si can optimize the welding process performance, reduce the viscosity of the slag, and improve the deslagging rate to more than 98%, while enhancing the fluidity of the weld seam metal to ensure that a smooth and edge-free joint can be formed during complex position welding such as vertical welding and horizontal welding of the pipeline, adapting to the on-site construction conditions. In addition, Si can also cooperate with Ni and Cr to improve the corrosion resistance of the weld seam, and the SiO2 slag can form a protective film on the surface of the weld seam, further blocking the penetration of corrosive media, making up for the lack of corrosion resistance of conventional welding wire relying only on metal elements, which is a composite function of Si not covered by existing public content.
[0029] Mn: Mn (manganese) is a key auxiliary element that balances weld toughness and process stability. It focuses on the needs of dredging pipeline vibration service and field welding. On the one hand, as an auxiliary deoxidizer, Mn can combine with oxygen and sulfur in the molten pool to form MnS and MnO, working with Si and Al to further reduce the content of harmful impurities in the weld and reduce the risk of intergranular corrosion caused by sulfide inclusions, which is crucial for the corrosion resistance of the weld of the dredging pipeline that is in contact with seawater for a long time. On the other hand, Mn can refine the weld grain, improve the low-temperature impact toughness of the weld (-40℃ impact energy ≥60J) by inhibiting excessive grain growth, avoid brittle fracture of the weld under vibration load during dredging operation, and solve the pain point of conventional welding wire "wear resistance but insufficient toughness". In addition, Mn can improve the fluidity of the weld metal, cooperate with the arc stabilizing effect of TiO2 in the flux, reduce arc fluctuation during welding, ensure smooth weld formation during vertical and horizontal welding of the pipeline, and reduce the defect rate of field welding. This is the unique value of Mn that is not emphasized in existing public content for the process requirements of dredging pipelines.
[0030] CaCo3: CaCo3 is a core slagging agent that builds an alkaline protective slag system, ensures weld corrosion resistance and welding stability, and focuses on the needs of dredging pipeline seawater corrosion and field welding. On the one hand, CaCO3 decomposes into CaO and CO2 at high welding temperatures, and CO2 can form a local protective atmosphere to isolate air from the molten pool, reducing the oxidation and burning loss of alloy elements such as Ni and Cr, ensuring that the corrosion-resistant element content of the weld meets the standards. The generated CaO as the main component of alkaline slag can neutralize acidic impurities (such as SiO2 and P2O5) in the molten pool, avoiding intergranular corrosion of the weld caused by acidic substances, and adapting to the service requirements in seawater environment. On the other hand, CaO can adjust the basicity of the slag to more than 2.5, improving the purification effect of the slag on the weld metal and reducing porosity and slag inclusion defects. At the same time, the gas generated by decomposition can moderately stir the molten pool, promote the uniform dispersion of hard phases (such as Ni3W), and avoid local lack of wear resistance. This is the complex function of CaCO3 that is not emphasized in existing public content for the dual requirements of "corrosion resistance + wear resistance" of dredging pipelines.
[0031] CaF2: CaF2 is the core functional component for optimizing the performance of the slag, ensuring the crack resistance and corrosion resistance of the weld. Its role focuses on the on-site welding of the dredging pipeline and the service requirements in seawater. On the one hand, CaF2 can significantly reduce the viscosity of the slag and improve the flowability of the slag, making the slag easy to fall off after welding (the slag removal rate is more than 98%), avoiding the local corrosion caused by the residual slag, and at the same time, it can absorb the hydrogen elements in the molten pool to inhibit the generation of hydrogen-induced cracks, adapting to the working conditions of the dredging pipeline after welding, which can withstand long-term vibration load. On the other hand, CaF2 and CaCO3 cooperatively regulate the basicity of the slag to ensure that the slag is strongly alkaline, which can effectively neutralize the acidic impurities (such as P2O5, SiO2) in the molten pool, reduce the damage of impurities to the corrosion resistance of the weld, and at the same time, it can reduce the burning loss of Cr elements, ensuring that the Cr content in the weld is stable at 18%-20%, maintaining the anti-seawater corrosion ability. This is the CaF2 composite function that the existing public content does not emphasize for the "corrosion resistance + crack resistance" dual requirements of the dredging pipeline.
[0032] TiO2: TiO2 is a core functional component that takes into account the stability of the welding process and the quality of the weld. Its role focuses on the complex welding scene and corrosion resistance requirements of the dredging pipeline, which is different from the existing patents that only emphasize "stable arc". On the one hand, TiO2 has excellent arc stability performance, which can reduce the arc ignition voltage and narrow the arc voltage fluctuation range (≤1V), avoiding problems such as arc breakage, excessive spatter, etc. during welding, ensuring that the arc is always stable during welding in complex positions such as vertical welding and horizontal welding of the pipeline, reducing defects such as incomplete fusion and undercut; on the other hand, TiO2 can adjust the melting point and flowability of the slag, forming an easy-to-remove slag system with CaCO3 and CaF2, which not only ensures the protective coverage of the slag on the molten pool, reducing the oxidation and burning loss of Ni and Cr elements, but also allows the slag to uniformly separate from the weld surface, avoiding local corrosion caused by residual slag, and at the same time, it can also refine the molten pool grains, helping to improve the low-temperature toughness of the weld (-40℃ impact energy ≥60J). This is the TiO2 composite function that the existing public content does not emphasize for the "process adaptation + corrosion resistance guarantee" dual requirements of the dredging pipeline.
[0033] The flux-cored wire in the present application has the following effects: 1. Enhance low-temperature toughness, resist vibration brittle fracture: Mn (0.5%-0.8%) and Si (0.8%-1.2%) in the core refine the weld grain, combined with the low burning loss characteristics of W (burning loss rate <3%) to avoid hard phase agglomeration, making the weld -40℃ impact energy ≥60J, much higher than the existing patent wire (≤40J), which can withstand the vibration load during dredging operation and avoid joint brittle fracture.
[0034] 2. Reduce hydrogen embrittlement sensitivity, adapt to wet environment: CaF2 in the core can adsorb hydrogen elements in the molten pool, cooperate with grain refinement to form a hydrogen embrittlement-resistant microstructure, so that the hydrogen embrittlement sensitivity of the weld is only 4.3%-7.2% (1.4-2.2 times of the pipe base material) after electrochemical hydrogen charging for 15h, effectively avoiding the generation of hydrogen-induced cracks in the dredging wet environment, and ensuring the long-term operation safety of the pipeline system.
[0035] 3. Build wear-resistant hard phase to resist silt erosion: W (2.0%-3.0%) in the core cooperates with Ni (58.0%-60.0%) and Mo (4.5%-5.5%) to form a Ni3W-MoC composite hard phase (hardness up to HV450 or more), and uniformly dispersed in the Ni matrix, so that the overall hardness of the weld surface is increased to HV320-HV350, and the wear resistance is increased by more than 25% compared with conventional nickel-based welding wire (HV250-HV280). At the same time, the particle size of the core powder is greater than 100 mesh and is uniformly mixed, avoiding hard phase agglomeration, ensuring uniform wear resistance of the entire weld area, reducing the joint wear rate from 0.15-0.2mm / month of conventional welding wire to less than 0.05mm / month, extending the service period to more than 5 years, and adapting to high-concentration silt conveying conditions.
[0036] 4. Form a multi-layer corrosion-resistant protective layer to resist seawater corrosion: The core cooperates with the high-alkaline slag system through the "Ni-Cr-Mo-Cu" four-element system to build a multi-layer corrosion-resistant protective layer: first, the face-centered cubic crystal structure of the Ni matrix is stable, Cr (18.0%-20.0%) forms a dense Cr2O3 passivation film, Mo promotes the repair of the passivation film to inhibit pitting corrosion, and Cu (1.0%-1.5%) forms an additional Cu2O auxiliary protective film, which cooperates with the four to make the corrosion rate of the weld in 3.5% sodium chloride solution ≤0.02mm / year, which is more than 60% higher than that of conventional welding wire (0.05-0.08mm / year); second, CaCO3 (3.5%-4.0%) and CaF2 (2.0%-2.5%) in the core form a high-alkaline slag system (alkalinity >2.5), reducing the oxidation loss of Ni and Cr (Cr loss rate from conventional 8%-12% to <5%), ensuring that the corrosion-resistant element content of the weld meets the standard, and adapting to the seawater and salt spray corrosion environment of marine dredging.
[0037] The second technical solution of the present application is a preparation method of a nickel-based alloy flux-cored wire for dredging pipeline welding, which is specifically implemented according to the following steps: Step 1, the following core powders are weighed according to the mass percentage: Ni: 58.0%-60.0%, Cr: 18.0%-20.0%, Mo: 4.5%-5.5%, W: 2.0%-3.0%, Cu: 1.0%-1.5%, Si: 0.8%-1.2%, Mn: 0.5%-0.8%, CaCO3: 3.5%-4.0%, CaF2: 2.0%-2.5%, TiO2: 1.0%-1.5%, the balance being inevitable impurities, but the total amount of impurities is controlled to be below 0.5%.
[0038] The powder particle size in the core is greater than 100 mesh; Step 2, drying the weighed core powder in step 1; The specific drying step is: heating to 160-210 DEG C in a vacuum tube furnace, and keeping for 2-3 hours; Step 3, the dried core powder in step 2 is loaded in a stirring bottle, and then placed in a V-shaped mixer for stirring for 20-40 minutes, the stirring speed ranges from 10-30 rpm, until the stirring is uniform; Step 4, the core powder prepared in step 3 is filled into a U-shaped sheath, and the sheath is closed by a mold to obtain a raw welding wire; Step 5, the raw welding wire is made into a wear-resistant and corrosion-resistant nickel-based alloy cored wire for dredging pipeline welding by a step-by-step reducing method.
[0039] The set diameter is 1.20 mm.
[0040] The application also provides a welding method for the nickel-based alloy cored wire for dredging pipeline welding, which is specifically implemented according to the following steps: Step 1), setting the TIG welding (tungsten inert gas welding) equipment parameters; The voltage is 12-16 V, the current is 110-180 A, and the wire dry extension is 8-15 mm; Step 2), according to the welding current size and the welding material quality, a tungsten electrode with a suitable diameter and the above-mentioned wear-resistant and corrosion-resistant nickel-based alloy for dredging pipeline welding are selected, and the protective gas is adjusted; The protective gas is argon, and the flow rate is controlled to be 5-15 L / min; Step 3), the welding piece is welded under the protective gas, and the angle and welding speed of the welding gun are kept stable during the welding process; generally, in order to make the argon better protect the molten pool, the effect is best when the center line of the tungsten electrode is perpendicular to the surface of the welding workpiece, but in the manual welding operation, too much perpendicularity will affect the welder's view. In actual operation, it is more appropriate to keep the welding gun and the workpiece surface at 80-85 DEG. According to the different thicknesses of the plates, the general welding speed is 35-40 cm / min.
[0041] Step 4, clean the surface of the welded part after welding is completed.
[0042] The application innovatively adopts TIG welding (tungsten inert gas welding) combined with a special nickel-based flux-cored wire: the non-melting electrode characteristics of TIG welding can precisely control the arc energy, and the arc stabilizing effect of TiO2 (1.0%-1.5%) in the flux core makes the arc voltage fluctuation ≤1V and the spatter rate ≤3%; at the same time, the high-alkaline slag system of CaCO3-CaF2 in the flux core and the argon protection of TIG welding cooperate to form "gas + molten slag" double protection, avoiding the contact of the molten pool with air, and solving the problems of "easy oxidation under single gas protection" in conventional MIG welding and "insufficient slag protection" in manual arc welding.
[0043] Specifically, 1. The wear and corrosion resistance is greatly improved: through precise temperature control by TIG welding and synergistic effect of flux core composition, the surface hardness of the weld reaches HV320-HV350 (25% higher than that of conventional TIG welding), the corrosion rate in 3.5% sodium chloride solution is ≤0.02mm / year (more than 60% lower than that of conventional welding), it can withstand high-concentration silt scouring and seawater corrosion, and the service period is extended to more than 5 years (conventional welding wire is less than 2 years).
[0044] 2. The mechanical properties are adapted to the vibration load: low voltage and low current parameters avoid overheating of the weld, and the flux core Mn and Si grain refinement effect, the weld impact energy at -40℃ is ≥60J (conventional TIG weld ≤45J), and the hydrogen embrittlement sensitivity after electrochemical hydrogen charging for 15h is only 4.3%-7.2% (1.4-2.2 times of the base material), which can resist the risk of hydrogen-induced cracking under the vibration of dredging operation and the wet environment.
[0045] Specific examples are as follows: Example 1 Step 1: First, the ingredients in the flux core are made into a powdery form with a particle size of ≤100 mesh, and then the flux core powder is weighed according to the mass percentage: Ni: 58.0%, Cr: 18.0%, Mo: 4.5%, W: 2.0%, Cu: 1.0%, Si: 0.8%, Mn: 0.5%, CaCO3: 3.5%, CaF2: 2.0%, TiO2: 1.0%, and the balance is unavoidable impurities, but the total amount of impurities is controlled to be less than 0.5%. The Inconel625 nickel-based alloy has a width of 7mm and a thickness of 0.3mm.
[0046] Step 2, dry the flux core powder weighed in step 1; The specific steps of drying are: heating to 160℃-210℃ in a vacuum tube furnace, and keeping the temperature for 2-3 hours; Step 3, put the dried flux core powder in step 2 into a stirring bottle, then put it in a V-type mixer and stir for 20-40 minutes, the stirring speed range is 10-30rpm, until the stirring is uniform; Step 4, fill the core powder obtained in step 2 into the Inconel 625 nickel-based alloy strip U-shaped groove, the filling rate is 19%, and after passing through the closed forming roller, a welding wire with a diameter of 1.2 mm is prepared; Step 5, during welding, under the process of voltage 13V, current 120A, welding wire dry elongation 10mm, welding gun angle 85°, welding speed 35cm / min.
[0047] The nickel-based alloy flux-cored wire prepared in Example 1 for welding dredging pipeline has a stable welding arc without arc breaking, a small amount of spatter (spatter rate ≤3%), and a beautiful weld appearance after welding, the surface is smooth without undercut, cracks, pores and other defects. Due to the synergistic effect of TiO2 arc stabilizing agent and uniformly mixed alloy powder in the core, no welding defects such as incomplete fusion and incomplete penetration occur, and the deslagging rate is more than 98%, without complex cleaning, it can meet the subsequent anticorrosion treatment requirements. The results of mechanical property and service performance detection of the weld after welding show that the tensile strength of the weld can reach 653MPa, and the elongation can reach 29.8%, which has good strength and toughness, and can withstand the vibration load and pressure fluctuation during the operation of the dredging pipeline. In the 3.5% sodium chloride solution simulating the marine dredging environment, the corrosion rate of the weld is only 0.018mm / year, and the surface hardness is HV325, which is more than 25% higher than the wear resistance of the conventional nickel-based welding wire, and more than 60% higher than the seawater corrosion resistance. At the same time, after 15h of electrochemical hydrogen charging test, the hydrogen embrittlement sensitivity of the weld is 7.3%, which is 1.3 times of the hydrogen embrittlement sensitivity of the base material of the dredging pipeline, and the hydrogen resistance performance is excellent, which can effectively avoid the risk of hydrogen induced cracking in the wet service environment. In summary, the flux-cored wire prepared in this embodiment completely meets the use requirements of the welding joint of the dredging pipeline, such as "wear resistance, corrosion resistance, vibration resistance and hydrogen embrittlement resistance", and can meet the welding requirements of dredging engineering pipeline in rivers, oceans and other scenes.
[0048] Example 2 Step 1: First, the core ingredients are made into a powder with a particle size of ≤100, then the core powder is weighed according to the mass percentage, Ni: 58.3%, Cr: 18.9%, Mo: 4.7%, W: 2.2%, Cu: 1.1%, Si: 0.9%, Mn: 0.6%, CaCO3: 3.6%, CaF2: 2.1%, TiO2: 1.1%, and the balance is unavoidable impurities, but the total amount of impurities is controlled to be less than 0.5%. The Inconel 625 nickel-based alloy strip has a width of 7mm and a thickness of 0.3mm.
[0049] Step 2, dry the core powder weighed in step 1; The specific steps of drying are: heating to 160-210℃ in a vacuum tube furnace, and keeping the temperature for 2-3 hours; Step 3, the dried core powder in step 2 is loaded into a stirring bottle and then placed in a V-type mixer for stirring for 20-40 minutes at a stirring speed ranging from 10-30 rpm until the stirring is uniform; Step 4, the core powder obtained in step 2 is filled into a U-shaped groove of an Inconel 625 nickel-based alloy strip at a filling rate of 25%, and after passing through a closed forming roller, a welding wire with a diameter of 1.2 mm is prepared; Step 5, during welding, welding is performed under the process of a voltage of 14 V, a current of 130 A, and a wire dry elongation of 11 mm. The welding torch angle is 85°, and the welding speed is 35 cm / min.
[0050] The nickel-based alloy flux-cored wire prepared in Example 2 for welding of dredging pipelines, relying on the fine adjustment of the core composition (the contents of elements such as Ni, Cr, and Mo are slightly higher than those in Example 1) and the higher filling rate design, exhibits better welding process adaptability: the welding arc is stable and has no fluctuation, the spatter rate is further reduced to ≤2.5%, the weld after welding is full and uniform, and there are no defects such as undercut, cracks, and pores on the surface; due to the increase of the core filling rate to 25%, the reaction of TiO2 arc stabilizing agent and alloy powder is more complete, completely avoiding the problems of incomplete fusion and incomplete penetration, the deslagging rate remains above 98%, and the cleaning efficiency meets the rapid construction requirements of dredging pipelines on site. The results of the weld performance test show that the tensile strength of the weld is increased to 678 MPa, the elongation rate is maintained at 29.5%, the strength and toughness match is better, and it can withstand greater pressure fluctuations and vibration loads when the dredging pipeline transports high-concentration silt; in a 3.5% sodium chloride solution simulating the marine dredging environment, the corrosion rate of the weld is reduced to 0.015 mm / year, the surface hardness is increased to HV338, the wear resistance of the weld is increased by more than 30% compared with that of conventional nickel-based welding wire, and the seawater corrosion resistance is increased by more than 65%; after 15 h of electrochemical hydrogen charging test, the hydrogen embrittlement sensitivity of the weld is 6.8%, which is only 1.2 times that of the base material of the dredging pipeline, and the anti-hydrogen embrittlement capability is better than that of Example 1. In summary, by fine-tuning the core composition and increasing the filling rate, this example further strengthens the performance of the weld in terms of wear resistance, corrosion resistance, and hydrogen embrittlement resistance, and is more suitable for the welding requirements of thick-walled pipelines in marine dredging projects, and the service reliability and application range are further widened.
[0051] Example 3 Step 1: First, the core ingredients are made into a powdery form with a particle size of ≤100 mesh, and then the core powder is weighed according to the mass percentage, Ni: 59.4%, Cr: 18.5%, Mo: 4.9%, W: 2.4%, Cu: 1.2%, Si: 0.93%, Mn: 0.64%, CaCO3: 3.7%, CaF2: 2.2%, TiO2: 1.2%, and the balance is unavoidable impurities, but the total amount of impurities is controlled to be below 0.5%. The Inconel 625 nickel-based alloy strip has a width of 7 mm and a thickness of 0.3 mm.
[0052] Step 2, dry the core powder weighed in step 1; The specific drying step is: heated to 160-210℃ in a vacuum tube furnace, and kept for 2-3 hours; Step 3, put the dried core powder in step 2 into a stirring bottle, then put it into a V-shaped mixer and stir for 20-40 minutes, the stirring speed range is 10-30 rpm, until it is stirred evenly; Step 4, fill the core powder obtained in step 2 into the U-shaped groove of Inconel 625 nickel-based alloy strip with a filling rate of 26%, and after passing through the closed forming roller, a 1.2mm welding wire is made; Step 5, during welding, weld under the process of voltage 15V, current 139A, wire dry elongation 13mm, welding gun angle 85°, welding speed 35cm / min.
[0053] The nickel-based alloy flux-cored wire prepared in Example 3 for welding dredging pipeline, with the precise adjustment of the core component (Ni increased to 66.4%, W increased to 2.4%) and the higher filling rate design, shows more excellent welding process stability: the welding arc has no fluctuation, the spatter rate is as low as ≤2%, the weld after welding is smooth and full, without defects such as undercut, crack, porosity, etc.; due to the filling rate increased to 26%, the CaCO3 slagging agent and TiO2 arc stabilizing agent in the flux core cooperate more fully, not only completely eliminating the problems of incomplete fusion and incomplete penetration, but also making the molten slag covering more uniform, the deslagging rate remaining above 98%, adapting to the high-efficiency welding demand of thick-walled joint site of dredging pipeline. The performance test results of the weld show that the tensile strength of the weld reaches 695MPa, and the elongation still remains 29.2%, the balance of strength and toughness is more optimal, and can withstand the severe vibration and high pressure load of the pipeline during high-concentration sand delivery; in the 3.5% sodium chloride solution simulating the strong corrosive marine dredging environment, the weld corrosion rate is as low as 0.012mm / year, the surface hardness is increased to HV345, the wear resistance of the weld is increased by more than 35% compared with the conventional nickel-based welding wire, and the seawater corrosion resistance is increased by more than 70%; after 15h electrochemical hydrogen charging test, the hydrogen embrittlement sensitivity of the weld is only 6.2%, which is 1.1 times of the hydrogen embrittlement sensitivity of the pipeline base material, and the anti-hydrogen embrittlement ability is further improved compared with Examples 1 and 2. In summary, by increasing the content of Ni and W and the filling rate, the core performance of wear resistance and corrosion resistance of the weld is strengthened, which is more suitable for the severe service requirements of marine high-concentration sand and thick-walled dredging pipeline, the service life and reliability are significantly improved compared with the previous two examples, and the application scenarios are further covered in deep-sea dredging engineering.
[0054] Example 4 Step 1: First, prepare the components of the core into a powder with a mesh size of ≤100. Then, weigh the core powder according to the following mass percentages: Ni: 59.6%, Cr: 19.3%, Mo: 5.3%, W: 2.6%, Cu: 1.3%, Si: 1.12%, Mn: 0.76%, CaCO3: 3.86%, CaF2: 2.4%, TiO2: 1.38%, with the remainder being unavoidable impurities, but the total impurity content should be controlled below 0.5%. The Inconel 625 nickel-based alloy strip has a width of 7 mm and a thickness of 0.3 mm.
[0055] Step 2: Dry the core powder weighed in Step 1; The specific drying steps are as follows: heat to 160℃-210℃ in a vacuum tube furnace and keep warm for 2-3 hours; Step 3: Place the dried core powder from Step 2 into a mixing flask, then place it in a V-type mixer and stir for 20-40 minutes at a speed of 10-30 rpm until it is uniformly mixed. Step 4: Fill the U-shaped groove of the Inconel 625 nickel-based alloy strip with a filling rate of 27% and make it into a 1.2mm welding wire after passing through the closed forming roller. Step 5: During welding, the welding process is carried out at a voltage of 15V, a current of 148A, a welding wire extension of 14mm, a welding torch angle of 85°, and a welding speed of 35cm / min.
[0056] The nickel-based alloy flux-cored welding wire prepared in Example 4, suitable for welding dredged pipelines, demonstrated top-notch welding process stability in the TIG welding of high-strength wear-resistant alloy steel weldments for dredged pipelines, thanks to further optimization of the core composition of the flux (Ni increased to 67%, Cr increased to 19.3%, W increased to 2.6%) and the design of the highest filler ratio: the welding arc remained stable throughout the entire process, the spatter rate was reduced to ≤1.5%, and the weld bead after welding was fine and full, without minor defects such as undercut, cracks, and porosity; due to the increased filler ratio of 27%, the synergistic effect of the CaCO3 alkaline slag-forming agent, TiO2 arc stabilizer, and Mo and W wear-resistant elements in the flux was more complete, which not only completely eliminated the problems of incomplete fusion and incomplete penetration, but also made the slag protection of the molten pool more comprehensive, and the slag removal rate remained stable at over 98%, which is fully adapted to the stringent requirements of efficient on-site welding of thick-walled deep-sea dredging pipelines. The performance test results of the weld show that the tensile strength of the weld is as high as 720 MPa, the elongation is still maintained at 28.8%, and the strength and toughness balance is optimal, so that the extreme pressure fluctuation and severe vibration load during the transportation of high-concentration silt in deep-sea dredging pipeline can be easily borne; in the 3.5% sodium chloride solution (superimposed with 0.5 MPa pressure) simulating the strong corrosion environment in deep sea, the corrosion rate of the weld is as low as 0.010 mm / year, the surface hardness is increased to HV352, the wear resistance of the weld is increased by more than 40% compared with that of the weld of the conventional nickel-based welding wire, and the seawater corrosion resistance is increased by more than 75%; after the electrochemical hydrogen charging test for 15 h, the hydrogen embrittlement sensitivity of the weld is only 5.8%, which is 1.05 times that of the hydrogen embrittlement sensitivity of the pipeline base material, and the hydrogen embrittlement resistance is improved by a breakthrough compared with the previous three embodiments. In summary, by further increasing the content and filling rate of core elements such as Ni, Cr and W, and cooperating with the optimized current of 148A, the “wear resistance, corrosion resistance and hydrogen embrittlement resistance” performance of the weld is pushed to a new high, perfectly adapting to the extreme service requirements of deep-sea high pressure, high-concentration silt and thick-walled dredging pipeline, the service life is prolonged by more than 20% compared with that of embodiment 3, and the application scenarios fully cover the core pipeline welding of deep-sea dredging engineering.
[0057] The nickel-based alloy flux-cored wire prepared in embodiment 4 (the core contains 67% Ni, 19.3% Cr and 2.6% W, and the filling rate is 27%), under the TIG welding process of 15V voltage and 148A current, the microstructure of the weld is observed (as shown in FIG. 1) and presents the typical “refined toughness structure” characteristics, which specifically show that: the weld structure is mainly composed of polygonal ferrite (PF), acicular ferrite (AF) and a small amount of fine pearlite (P), and the distribution of each phase structure is uniform, without obvious composition segregation or coarse grain area. Figure 1
[0058] From the mechanism of structure formation, the synergistic effect of high content of Ni (67%) and Cr (19.3%) in the core significantly reduces the phase transition temperature of the weld metal, and the “slow cooling crystallization environment” brought by the optimized current of 148A creates conditions for the large generation of acicular ferrite. The acicular ferrite (AF) is formed by shear transformation and diffusion transformation, and presents a non-equiaxed parallel thin needle shape, and contains high-density dislocations inside; compared with the coarse polygonal ferrite easily appearing in the weld of the conventional nickel-based welding wire, the acicular ferrite in the weld of the embodiment is smaller in size (the average grain size is ≤5 μm), and is distributed in the weld matrix, becoming the core “toughness phase” of the weld toughness. At the same time, the addition of 2.6% W in the core further refines the pearlite structure, so that the pearlite (P) distributed in the weld is in a fine and dispersed state, avoiding the weakening of the weld toughness by coarse pearlite. This “acicular ferrite + fine pearlite” composite structure directly gives the weld a high elongation of 28.8%, ensuring that it is not easy to be brittle fractured under the severe vibration load of the deep-sea dredging pipeline.
[0059] From the influence of the microstructure on the performance, the microstructure plays a key role in improving the hydrogen performance of the weld: on the one hand, a large number of fine ferrite structures (including polygonal ferrite and acicular ferrite) in the weld provide a large number of diffusion sites for hydrogen atoms, which can be uniformly dispersed at the phase interface and dislocation, and it is difficult to form local aggregation, effectively reducing the hydrogen pressure in the phase structure, avoiding the formation of deep and large corrosion points due to hydrogen aggregation; on the other hand, the high-density dislocations in the acicular ferrite enhance the "dislocation transport capacity" of hydrogen atoms, further reducing the accumulation of hydrogen atoms at grain boundaries and defects, and reducing the probability of hydrogen-induced corrosion and hydrogen-induced cracking. In addition, the Cr2O3 passivation film formed by 19.3% Cr in the core cooperates with the refined structure, not only blocks the penetration of corrosive media, but also reduces the channel for hydrogen atoms to enter the weld matrix, ultimately reduces the hydrogen embrittlement sensitivity of the weld to 5.8%, which is only 1.05 times that of the base material, perfectly adapting to the hydrogen resistance requirements of the dredging pipeline in the deep-sea high-pressure and high-humidity environment.
[0060] The present application develops a nickel-based alloy flux-cored wire which has high wear resistance, high corrosion resistance and excellent welding process performance, solves the problems of insufficient wear resistance, poor corrosion resistance and weak process adaptability of conventional welding wires in the welding of dredging pipelines, and meets the long service life and high reliability requirements of pipeline welded joints in dredging engineering.
[0061] The beneficial effects of the present application are: 1. The nickel-based alloy flux-cored wire in the present application has a short preparation period and high production efficiency, and can realize continuous production. 2. The nickel-based alloy flux-cored wire designed in the present application has good process performance, is suitable for various welding positions such as flat welding and vertical welding of dredging pipelines, the arc is stable without arc breaking during the welding process, the spatter amount is small (spatter rate ≤ 3%), the deslagging after welding is smooth (deslagging rate is more than 98%), and no additional cleaning is required for subsequent corrosion prevention treatment; the weld is well formed, the surface is smooth and smooth without undercutting, porosity and other defects, the weld reinforcement is controlled within 1-3 mm, and the width is uniform, which meets the appearance quality and sealing requirements of the pipeline welded joints.
[0062] The weld, as the weak area of the dredging pipeline steel, has an hydrogen resistance not less than that of the pipeline base material, and after electrochemical hydrogen charging for 15h in the simulated humid environment of dredging engineering, the hydrogen embrittlement sensitivity of the weld metal is only 4.3%-7.2%, which is 1.4-2.2 times that of the hydrogen embrittlement sensitivity of the pipeline base material; this is due to the adsorption of hydrogen elements by fluorite (CaF2) in the core and the hydrogen embrittlement-resistant microstructure formed after the grain refinement of rare earth ferrosilicon alloy, which can effectively avoid the failure of the welded joint due to hydrogen-induced cracking in the long-term humid service environment of the dredging pipeline, and ensure the long-term operation safety of the pipeline system.
[0063] The above merely describes preferred specific embodiments of the present application, but the protection scope of the present application is not limited thereto, and any person skilled in the art, according to the technical solution and inventive concept of the present application, makes equivalent replacement or change within the technical range disclosed by the present application, which should be covered within the protection scope of the present application.
Claims
1. A nickel-based alloy flux-cored welding wire for dredging pipeline welding, comprising a welding sheath and a flux core, characterized in that, The core comprises the following components by weight percentage: Ni: 58.0%-60.0%, Cr: 18.0%-20.0%, Mo: 4.5%-5.5%, W: 2.0%-3.0%, Cu: 1.0%-1.5%, Si: 0.8%-1.2%, Mn: 0.5%-0.8%, CaCO3: 3.5%-4.0%, CaF2: 2.0%-2.5%, TiO2: 1.0%-1.5%, with the balance being unavoidable impurities.
2. The nickel-based alloy flux-cored welding wire for dredging pipeline welding according to claim 1, characterized in that, The powder in the core has a particle size greater than 100 mesh.
3. The nickel-based alloy flux-cored welding wire for dredging pipeline welding according to claim 1, characterized in that, The solder sheet is an Inconel 625 nickel-based alloy strip with a width of 7 mm and a thickness of 0.3 mm.
4. The nickel-based alloy flux-cored welding wire for dredging pipeline welding according to claim 1, characterized in that, The filling rate of the flux core powder inside the weld bead is 18wt%-25wt%.
5. A method for preparing a nickel-based alloy flux-cored welding wire for welding dredged pipelines as described in any one of claims 1-4, characterized in that, include: Step 1: Weigh the following core powders according to their mass percentages: Ni: 58.0%-60.0%, Cr: 18.0%-20.0%, Mo: 4.5%-5.5%, W: 2.0%-3.0%, Cu: 1.0%-1.5%, Si: 0.8%-1.2%, Mn: 0.5%-0.8%, CaCO3: 3.5%-4.0%, CaF2: 2.0%-2.5%, TiO2: 1.0%-1.5%, with the balance being unavoidable impurities; The powder particle size in the core is greater than 100 mesh; Step 2: Dry the core powder weighed in Step 1; Specifically, heat the material in a vacuum tube furnace to 160℃-210℃ and hold it for 2-3 hours. Step 3: Place the dried core powder from Step 2 into a mixing flask, then place it in a V-type mixer and stir for 20-40 minutes at a speed of 10-30 rpm until it is uniformly mixed. Step 4: Fill the U-shaped welding skin with the flux core powder prepared in Step 3, and close the welding skin with a mold to obtain the original welding wire; Step 5: The original welding wire is gradually reduced in diameter to produce a nickel-based alloy flux-cored welding wire of a set diameter for welding dredging pipelines.
6. A method for welding dredged pipelines, characterized in that, The method employs the nickel-based alloy flux-cored welding wire for dredging pipeline welding as described in any one of claims 1-4, comprising: Step 1) Set the parameters for the TIG welding equipment; Step 2) Select tungsten electrode and nickel-based alloy flux-cored welding wire according to the welding current and the material of the workpiece, and adjust the shielding gas; Step 3) Weld the workpiece under a protective gas atmosphere; Step 4) Clean the surface of the weldment after welding is completed.
7. The dredging pipeline welding method according to claim 6, characterized in that, In step 1), the voltage is 12V-16V, the current is 110A-180A, and the wire extension is 8mm-15mm.
8. The dredging pipeline welding method according to claim 6, characterized in that, In step 2), the protective gas is argon, and the flow rate is controlled between 5L / min and 15L / min.
Citation Information
Patent Citations
Nickel base welding rod of Ni-Cr-Mo alloy system
CN102962603B
Nickel-chromium-molybdenum-niobium corrosion resistant welded alloy and manufacturing method thereof
CN104342584A
Flux cored wire for nickel base alloys
CN105643141B